Transformation of Lithuanian Education Monitoring: Trends and Prerequisites - Survutaitė, Dalia (Acta Paedagogica Vilnensia, 2012)
Following the good world practice, the National School for School Evaluation initiated the creation of a specific model for external school evaluation. Over the last decade, the (self-)assessment of school activity has become a usual element in the work of education institutions. The Lithuanian system of education focuses not only on the efficient implementation of the government policy on education, but also on orienting the latest education reforms towards improving the quality of educational services. Under the fast transformations from the authoritarian regime to a democratic system in Lithuania, the education system positions itself at the junction of educational paradigms. The created modern instrument for education quality management – external assessment of school activities – meets the concept of the free education paradigm or, according to M. Lukšienė, complies with the concept of creative education, whereas the construct of educa tion process evaluation, which is applied to teachers, targets more at the identification of the features of normative education activities. The results of teachers’ opinion survey clearly show that teachers fear unified and standardised requirements as regards educational activity and a wide range of assessment spheres. External assessment of the quality of school activities, which has been created and improved following the most modern systems of Western Europe, is particularly important and optimal while reforming the Lithuanian system of education.The article analyses the model of the external assessment of schools, which is being created by the National Agency for School Evaluation. A number of conclusions drawn on the basis of the teachers’ opinion survey are also presented.
Keywords: education monitoring; school; quality of school activities; external assessment; transformation